Incidental Findings from 16,400 Brain MRI Examinations of Research Volunteers - Rowley, P.A.; Paukner, M.J.; Eisenmenger, L.B.; Field, A.S.; Davidson, R.J.; Johnson, S.C.; Asthana, S.; Chin, N.A.; Prabhakaran, V.; Bendlin, B.B.; Postle, B.R.; Goldsmith, H.H.; et al. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Incidental findings are discovered in neuroimaging research, ranging from trivial to life-threatening. We describe the prevalence and characteristics of incidental findings from 16,400 research brain MRIs, comparing spontaneous detection by nonradiology scanning staff versus formal neuroradiologist interpretation.MATERIALS AND METHODS: We prospectively collected 16,400 brain MRIs (7782 males, 8618 females; younger than 1 to 94 years of age; median age, 38 years) under an institutional review board directive intended to identify clinically relevant incidental findings. The study population included 13,150 presumed healthy volunteers and 3250 individuals with known neurologic diagnoses. Scanning staff were asked to flag concerning imaging findings seen during the scan session, and neuroradiologists produced structured reports after reviewing every scan.RESULTS: Neuroradiologists reported 13,593/16,400 (83%) scans as having normal findings, 2193/16,400 (13.3%) with abnormal findings without follow-up recommended, and 614/16,400 (3.7%) with “abnormal findings with follow-up recommended.” The most common abnormalities prompting follow-up were vascular (263/614, 43%), neoplastic (130/614, 21%), and congenital (92/614, 15%). Volunteers older than 65 years of age were significantly more likely to have scans with abnormal findings (P < .001); however, among all volunteers with incidental findings, those younger than 65 years of age were more likely to be recommended for follow-up. Nonradiologists flagged <1% of MRIs containing at least 1 abnormality reported by the neuroradiologists to be concerning enough to warrant further evaluation.CONCLUSIONS: Four percent of individuals who undergo research brain MRIs have an incidental, potentially clinically significant finding. Routine neuroradiologist review of all scans yields a much higher rate of significant lesion detection than selective referral from nonradiologists who perform the examinations. Workflow and scan review processes need to be carefully considered when designing research protocols.CHSCardiovascular Health StudiesNPVnegative predictive valuePIprincipal investigatorPPVpositive predictive valueSEstandard error